Performance Investigation of Hybrid Flow Control Method in Curve Diffuser: Guide Vanes and Mesh Screen - Nordin, Normayati; Harun, Nur Faqihah (Journal of Emerging Technologies and Industrial Applications, 2025)
This research investigates a hybrid flow control method that combines mesh screens and guide vanes in curve diffusers, addressing the challenges posed by diffusers with a 90-degree angle bend. The severe curvature in such diffusers often leads to flow separation, reduced flow homogeneity, and increased potential flow loading. By utilizing Computational Fluid Dynamics (CFD) software for numerical analysis, the study evaluates the effectiveness of the hybrid flow control method in improving curve diffuser performance and proposes an optimum device configuration. The research focuses on assessing the impact of guide vanes and mesh screens on flow separation and pressure loss, aiming to provide insights into system efficiency. The findings not only contribute to future research on curved diffusers but also support environmentally sustainable practices. By highlighting the potential of the hybrid flow treatment method in reducing flow separation, improving static pressure, and enhancing the overall performance of curve diffusers, this study offers valuable information for designing more efficient engineering systems